Nanoscale investigations of complex microbial interactions with terrestrial and extraterrestrial minerals using STEM based approach: implications for life on Earth and beyond - Milojevic, Tetyana; Albu, Mihaela; Letofsky-Papst, Ilse; Mashchenko, Artem (Frontiers in Environmental Chemistry, 2025)
Our recent investigations using scanning transmission electron microscopy (STEM) based approach address tungsten-microbial interactions as a microbial strategy to withstand harsh environments, microbial metal extraction capacities for bioleaching/biomining operations, astrobiological implication of microbial-mineral interactions, and Mars-relevant biosignatures as traces of life that can be detected in the physicochemical conditions beyond Earth. By means of STEM based nanoscale resolution ultrastructural studies coupled to energy dispersive spectroscopy (EDS) and electron energy loss spectroscopy (EELS), we have investigated remarkable metal redox events and unique ultrastructural features of the mineral-microbial interfaces with regard to the mechanisms of mineral biotransformation mediated by various chemolithoautotrophs; the subcellular localization of metal incorporation and binding sites; the chemical nature of the metal complexes formed at the microbe-mineral interfaces; and biomineral patterns formed during the biotransformation of terrestrial minerals and astromaterials. Our results indicate that microbial cells form a robust, metal-bearing cell crust that may help microorganisms withstand harsh environments and serve as potential biosignature for the search of life. During the biomineralization of the microbial cell surface with tungsten, a tungsten-encrusted layer with a thickness of 37 ± 7 nm and a W content of 76.3% (Wt) was formed around the Metallosphaera sedula cells. When cultivated on the genuine Noachian Martian breccia Northwest Africa (NWA) 7,034, M. sedula cells were encrusted in a mineral layer of 28 ± 2 nm thickness and a P, Fe, Mn, and Al content of 9.62% (Wt), 11.65% (Wt), 4.29% (Wt), and 2.82% (Wt), respectively. During these investigations, we have developed an efficient combined approach of microbiology, wet chemistry and STEM based spectroscopy nanoanalysis. This work highlights the biologically-mediated processing of (extra)terrestrial materials, provides implications for natural samples and biotechnological processes, and represents a special interest for space exploration missions.